Magnitude and Origin of CO2 Evasion From High‐Latitude Lakes. Issue 6 (27th June 2022) - Verheijen, H. A.; Klaus, M.; Seekell, D. A.; Karlsson, J.
Abstract: Lakes evade significant amounts of carbon dioxide (CO2 ) to the atmosphere; yet the magnitude and origin of the evasion are still poorly constrained. We quantified annual CO2 evasion and its origin (in‐lake net ecosystem production vs. lateral inputs from terrestrial ecosystems) in 14 high‐latitude lakes through high‐frequency estimates of open water CO2 flux and ecosystem metabolism and inorganic carbon mass‐balance before and after ice breakup. Annual CO2 evasion ranged from 1 to 25 g C m −2 yr −1 of which an average of 57% was evaded over a short period at ice‐breakup. Annual internal CO2 production ranged from −6 to 21 g C m −2 yr −1, of which at least half was produced over winter. The contribution of internal versus external source contribution to annual CO2 evasion varied between lakes, ranging from fully internal to fully external with most lakes having over 75% of the evasion sustained through a single source. Overall, the study stresses the large variability in magnitude and control of CO2 evasion and suggests that environmental change impacts on CO2 evasion from high‐latitude lakes are not uniform. Plain Language Summary: Lakes release significant amounts of carbon dioxide (CO2 ) to the atmosphere. This CO2 evasion is mainly sustained by carbon from land, either via external inputs of CO2 rich water or by internal breakdown of imported organic carbon to CO2 . The extent of CO2 emission and the contribution of these two sources are poorly understood in regard to the numerous lakes at high latitudes. We studied 14 high‐latitude lakes and found that all lakes emitted CO2 on an annual basis and that 0%–100% (average 44%) of this CO2 came from breakdown of organic carbon in the lakes. The spring ice‐breakup period contributed, on average, 57% of the annual emitted CO2 despite covering only 16% of the open water season duration. Our study defines the fundamental role of lakes on the landscapes as "reactors" or "chimneys" for carbon processing and emission to the atmosphere, and how these roles change over the course of the year. Key Points: Carbon dioxide evasion during spring ice breakup dominates annual evasion Carbon dioxide evasion is sourced by both external input and internal lake metabolism with large variability between lakes Seasonally resolved estimates are needed in order to understand the role of high‐latitude lakes in landscape carbon budgets